2022
DOI: 10.1055/a-1816-6700
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Teriparatide on Subsequent Fracture and Bone Mineral Density in 47 Women with Pregnancy- and Lactation-associated Osteoporosis and Vertebral Fractures

Abstract: Introduction Pregnancy- and lactation-associated osteoporosis (PLO) with predominantly vertebral fractures is a rare but severe disease which can occur in the last trimester of pregnancy or postpartum. The aim of the present study was to assess the impact of teriparatide on subsequent fractures and bone mineral density (BMD) in patients with PLO. Materials and Methods A total of 47 patients with PLO and postpartum spinal fractures (mean: 4 fractures) undergoing treatment with teriparatide were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 37 publications
1
14
0
Order By: Relevance
“…According to our methods, we identified the following 12 original studies (Table 1). [38][39][40][41][42][43][44][45][46][47][48][49]).…”
Section: Results: Pao and Loamentioning
confidence: 99%
“…According to our methods, we identified the following 12 original studies (Table 1). [38][39][40][41][42][43][44][45][46][47][48][49]).…”
Section: Results: Pao and Loamentioning
confidence: 99%
“…Anecdotal and uncontrolled use of bisphosphonates, teriparatide, denosumab, romosozumab, strontium ranelate, and calcitonin have been reported with 10–30 % increases in BMD achieved, but whether this exceeds what would have occurred naturally after weaning remains unknown ( 73 , 81 ). One large case series reported no difference in the magnitude of increase in BMD after use of bisphosphonates, teriparatide, or combination therapy, but found twice as many fractures subsequently occurred in those who had been treated compared to those who were not treated ( 77 ).…”
Section: Osteoporosis Associated With Pregnancy and Lactationmentioning
confidence: 99%
“…Use of antiresorptive medications could conceivably blunt post-weaning recovery, given that combination therapy blunted the effect of osteoanabolic treatment in women with osteoporosis ( 27 ). In postmenopausal women, any gains in BMD achieved with osteoanabolic treatment are lost in 12–18 months unless antiresorptive treatment is initiated, but limited data from women with osteoporosis associated with pregnancy and lactation suggest that the effects of osteoanabolic treatment may persist without need for antiresorptive medication ( 81 ). However, the reported follow-up was only one year.…”
Section: Osteoporosis Associated With Pregnancy and Lactationmentioning
confidence: 99%
See 1 more Smart Citation
“…More frequently, anabolic agents are used to treat PLO and have demonstrated clinical improvement in pain and increases in BMD ( Stumpf et al, 2007 ; Hellmeyer et al, 2010 ; Choe et al, 2012 ; Lampropoulou-Adamidou et al, 2012 ; Lee et al, 2013 ; Bonacker et al, 2014 ; Pola et al, 2016 ; Ijuin et al, 2017 ; Laroche et al, 2017 ; Hong et al, 2018 ; Cerit and Cerit, 2020 ; Tuna et al, 2020 ). Two recently published studies have demonstrated that use of teriparatide results in improved bone density as compared to calcium and vitamin D alone ( Lee et al, 2021 ; Hadji et al, 2022 ). It is also notable that the study from Lee and colleagues demonstrated that teriparatide could be used in this setting to increase bone density and that subsequent use of an antiresorptive medication may not be necessary as patients who did not receive an anti-resorptive agent did not lose bone for up to 2 years after discontinuing anabolic therapy with PTH ( Lee et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%